2019
DOI: 10.1016/j.neo.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Trastuzumab-Induced Alterations in Intratumoral Heterogeneity with Quantitative Imaging and Immunohistochemistry in HER2+ Breast Cancer

Abstract: The purpose of this study is to investigate imaging and histology-based measurements of intratumoral heterogeneity to evaluate early treatment response to targeted therapy in a murine model of HER2+ breast cancer. BT474 tumor-bearing mice (N = 30) were treated with trastuzumab or saline and imaged longitudinally with either dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) or 18F-fluoromisonidazole (FMISO) positron emission tomography (PET). At the imaging study end point (day 4 for MRI or 7 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Otsu thresholding [ 83 ] was used for automated segmentation of proliferative cell nuclei from anti-Ki-67 stained sections and microvessels from anti-CD31 stained sections. Further details of the automated segmentation techniques are described in previous work [ 26 ]. Masks of whole tissue for each stained tissue slice were semi-automatically generated using gray (non-tissue) area masks and manually drawn ROIs ( Figure S7c ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otsu thresholding [ 83 ] was used for automated segmentation of proliferative cell nuclei from anti-Ki-67 stained sections and microvessels from anti-CD31 stained sections. Further details of the automated segmentation techniques are described in previous work [ 26 ]. Masks of whole tissue for each stained tissue slice were semi-automatically generated using gray (non-tissue) area masks and manually drawn ROIs ( Figure S7c ).…”
Section: Methodsmentioning
confidence: 99%
“…Approaches to quantify intratumoral heterogeneity from imaging data include histogram and texture analysis [ 22 ]. Histogram analysis involves quantitative assessment of parameter map distributions, demonstrating value over whole-tumor summary statistics [ 23 , 24 ], and allowing for the quantification of longitudinal alterations in intratumoral heterogeneity [ 25 , 26 ]. However, this approach forgoes the spatial information provided in imaging data.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the expression of cell surface markers and spatial distribution of cells over time, we developed an algorithm that automatically bins nuclei segmented images and generates density maps in the StEMM. Interestingly, when collating density maps from histological sections, the bin size is often set manually in the range of 50 to 150 μm 54‐56 . In contrast, by the use of our algorithm, bin size was automatically set between 45 and 115 μm.…”
Section: Discussionmentioning
confidence: 99%
“…This particular study showed that quantitative data from in vivo imaging is consistent with data derived from quantitative studies in histologic sections to study intratumoral heterogeneity. 54 …”
Section: Applications Of Biomarker Imaging Analysismentioning
confidence: 99%